Some Reflections on BDS and Feminist Political Solidarity - Bhandar, Brenna (feminists@law, 2014)
The main theme that I address in this paper is the boycott as a form of political solidarity. Recalling one of the primary objectives of Black and Third World feminist activists and scholars, I explore how BDS is one of the primary ways of building solidarity with Palestinians living under occupation. The logic of BDS is that of a unified, anti-racist and anti-colonial politics, which counters the logic of the Oslo Accords, one of fragmentation along multiple axes.